Administration of low intensity vibration and a RANKL inhibitor, alone or in combination, reduces bone loss after spinal cord injury-induced immobilization in rats - Yuanzhen Peng; Helen M. Bramlett; W. Dalton Dietrich; Alex Marcillo; Juliana Sanchez-Molano; Ofelia Furones-Alonso; Jay J. Cao; Jenney Huang; Andrew A. Li; Jian Q. Feng; William A. Bauman; Weiping Qin (Bone Reports)
We previously reported an ability of low-intensity vibration (LIV) to improve selected biomarkers of bone turnover and gene expression and reduce osteoclastogenesis but lacking of evident bone accrual. In this study, we demonstrate that a prolonged course of LIV that initiated at 2 weeks post-injury and continued for 8 weeks can protect against bone loss after SCI in rats. LIV stimulates bone formation and improves osteoblast differentiation potential of bone marrow stromal stem cells while inhibiting osteoclast differentiation potential of marrow hematopoietic progenitors to reduce bone resorption. We further demonstrate that the combination of LIV and RANKL antibody reduces SCI-related bone loss more than each intervention alone. Our findings that LIV is efficacious in maintaining sublesional bone mass suggests that such physical-based intervention approach would be a noninvasive, simple, inexpensive and practical intervention to treat bone loss after SCI. Because the combined administration of LIV and RANKL inhibition better preserved sublesional bone after SCI than either intervention alone, this work provides the impetus for the development of future clinical protocols based on the potential greater therapeutic efficacy of combining non-pharmacological (e.g., LIV) and pharmacological (e.g., RANKL inhibitor or other agents) approaches to treat osteoporosis after SCI or other conditions associated with severe immobilization.